Monetary policy effects on firms' uncertainty - Gabriela López-Noria; Mathieu Pedemonte (Inter-American Development Bank (IDB), 2025)
We study how monetary policy affects inflation uncertainty. Using a survey of Mexican firms and exploiting quasi-random variation in the response date, we estimate the effect of a monetary policy decision and surprise on firms perceived inflation uncertainty. We find that a one percentage point contractionary monetary policy reduces inflation uncertainty by 0.02 percentage points. We explore how this result is affected by levels of higher and lower aggregate uncertainty. We find that monetary policy tightening is twice as effective in reducing inflation uncertainty in periods of higher economic uncertainty, such as trade uncertainty. Our findings highlight the role of monetary policy in reducing inflation uncertainty. We discuss that in periods of uncertainty, monetary authorities face a trade-off between stimulating the economy and increasing uncertainty about the inflation outlook.
Keywords: E31; D80; D84; E52; 330; Inflation uncertainty; Firms' expectations; Monetary policy; Survey data